2011
DOI: 10.1007/s00394-011-0223-2
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diets affect energy and bone metabolism in growing rats

Abstract: BT diet rich in saturated fatty acids had decreased digestibility and adversely affected energy and bone metabolisms, in growing healthy male rats. There were no changes in zoometric and bone parameters among rats fed high vegetable oil diets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 34 publications
1
39
1
4
Order By: Relevance
“…The flaxseed group had greater BMD and BMC, as well as improved markers of biomechanical strength such as higher peak load at the femur midpoint. However, another study that utilized a 20% fat diet from flaxseed oil, rich in ALA, did not show any effect on BMD, BMC or biomechanical strength in growing male rats from 3-11 weeks of age, relative to corn oil fed rats [25]. Overall, due to the limited number of studies showing a weak or absent effect of ALA, it is not possible yet to conclude a definitive role for ALA in bone health.…”
Section: Ala Studiesmentioning
confidence: 93%
See 1 more Smart Citation
“…The flaxseed group had greater BMD and BMC, as well as improved markers of biomechanical strength such as higher peak load at the femur midpoint. However, another study that utilized a 20% fat diet from flaxseed oil, rich in ALA, did not show any effect on BMD, BMC or biomechanical strength in growing male rats from 3-11 weeks of age, relative to corn oil fed rats [25]. Overall, due to the limited number of studies showing a weak or absent effect of ALA, it is not possible yet to conclude a definitive role for ALA in bone health.…”
Section: Ala Studiesmentioning
confidence: 93%
“…In addition to studies demonstrating that changes in dietary fatty acid composition are reflected in bone tissue, studies have examined the effects of ALA alone on bone development, which have yielded mixed results [17,20,21,[23][24][25]42] (Table 2). Thirty-week-old female rats exposed to flaxseed oil or soybean oil from the last ten days of gestation to three weeks postnatal had greater BMD at the femur mid-diaphysis than their littermates fed sunflower seed oil [20].…”
Section: Ala Studiesmentioning
confidence: 99%
“…Moreover, at the end of the experiment, the mice in the HFD group were associated with decreased stiffness and maximum force, indicating an effect on the flexural strength of femurs, which suggested that HFD not only affected bone quantity, but also bone quality [1]. Macri et al [2] found that rats that consumed a high-saturated fatty acid diet (beef tallow) for eight weeks had the lowest total skeleton bone mineral content (BMC) and cancellous bone mineral density (spine BMD) compared with rats that consumed other types of vegetable oils. The bone mineral changes in rats might be involved in intestinal soap formation with calcium, which impaired absorption.…”
Section: Studies In Animalsmentioning
confidence: 99%
“…A moderately high fat ad libitum feeding also results in changes of the duodenal oxidation state that lowers Ca absorption in mice [5]. In addition, studies suggest that HFD that are typically rich in saturated fatty acids (SFAs), negatively affect bone mineral density (BMD) during growth in rat studies [6]. This is supported by observational studies in adult humans showing that a high fat intake is negatively associated with BMD [7, 8].…”
Section: Introductionmentioning
confidence: 99%